Performance of Size 1 I-Gel Compared with Size 1 ProSeal Laryngeal Mask in Anesthetized Infants and Neonates - Gulay Erdogan Kayhan; Zekine Begec; Mukadder Sanli; Ender Gedik; Mahmut Durmus (The Scientific World Journal)
Purpose. The size 1 I-gel, recommended for small infants and neonates weighing 2–5 kg, has recently been released. There are no prospective studies available that assess the insertion conditions, sealing pressures, or ventilation quality of it. This study was designed to compare the performance of recently released size 1 I-gel with size 1 ProSeal LMA. Methods. Fifty infants and neonates, ASA I-II were included in this prospective, randomized, and controlled study. Patients were divided into two groups for placing I-gel or ProSeal LMA. The primary outcome was airway leak pressure, and secondary outcomes included insertion time, insertion success and conditions, initial airway quality, fiberoptic view of the larynx, and complications. Results. There were no significant differences in terms of airway leak pressure between the I-gel (27.44±5.67) and ProSeal LMA (23.52±8.15) (P=0.054). The insertion time for the I-gel was shorter (12.6±2.19 s) than for the ProSeal LMA (24.2±6.059 s) (P=0.0001). Insertion success and conditions were similar in groups. We encountered few complications. Conclusion. Our study demonstrates that the size 1 I-gel provided an effective and satisfactory airway as the size 1 ProSeal LMA. It may be a good alternative supraglottic airway device for use in small infants and neonates. This trial is registered with: ClinicalTrials.gov NCT01704118.